Atmospheric plasma treatment of carbon fibers for enhancement of their adhesion properties - Santos, Alberto Lima [UNESP]; Botelho, Edson Cocchieri [UNESP]; Kostov, Konstantin G. [UNESP]; Nascente, Pedro A. P.; Da Silva, Leide Lili G. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Plasma processing of carbon fibers (CFs) is aimed to provide better contact and adhesion between individual plies without decrease in the CF mechanical resistance. This paper deals with surface modification of CFs by an atmospheric pressure dielectric barrier discharge (DBD) for enhancing the adhesion between the CF and the polymeric matrix. The scanning electron microscopy of the treated samples revealed many small particles distributed over entire surface of the fiber. These particles are product of the fiber surface etching during the DBD treatment that removes the epoxy layer covering as-received samples. The alteration of the CF surface morphology was also confirmed by the Atomic force microscopy (AFM), which indicated that the CF roughness increased as a result of the plasma treatment. The analysis of the surface chemical composition provided by X-ray photoelectron spectroscopy showed that oxygen and nitrogen atoms are incorporated onto the surface. The polar oxygen groups formed on the surface lead to the increasing of the CF surface energy. The results of interlaminar shear strength test (short beam) of CFs/polypropylene composites demonstrated a greater shear resistance of the composites made with CFs treated by DBD than the one with untreated fibers. Both the increase in surface roughness and the surface oxidation contribute for the enhancement of CF adhesion properties. © 2012 IEEE.
Keywords: Carbon compounds; plasma applications; surface treatment; Adhesion properties; Atmospheric plasma treatments; Atmospheric pressure dielectric barrier discharges; Epoxy layers; Fiber surface; Inter-laminar shear strengths; Mechanical resistance; Oxygen and nitrogens; Oxygen groups; Plasma treatment; Polymeric matrices; Shear resistances; Short beams; Small particles; Surface chemical composition; Surface oxidations; Adhesion; Atmospheric pressure; Atomic force microscopy; Carbon fibers; Oxygen; Photoelectrons; Scanning electron microscopy; Surface roughness; Surface treatment; X ray photoelectron spectroscopy; Plasma applications